A dynamic model‐based approach to motion and deformation tracking of prosthetic valves from biplane x‐ray images. Issue 6 (3rd May 2018) - Wagner, Martin G.; Hatt, Charles R.; Dunkerley, David A. P.; Bodart, Lindsay E.; Raval, Amish N.; Speidel, Michael A.
Abstract : Purpose: Transcatheter aortic valve replacement (TAVR) is a minimally invasive procedure in which a prosthetic heart valve is placed and expanded within a defective aortic valve. The device placement is commonly performed using two‐dimensional (2D) fluoroscopic imaging. Within this work, we propose a novel technique to track the motion and deformation of the prosthetic valve in three dimensions based on biplane fluoroscopic image sequences. Methods: The tracking approach uses a parameterized point cloud model of the valve stent which can undergo rigid three‐dimensional (3D) transformation and different modes of expansion. Rigid elements of the model are individually rotated and translated in three dimensions to approximate the motions of the stent. Tracking is performed using an iterative 2D–3D registration procedure which estimates the model parameters by minimizing the mean‐squared image values at the positions of the forward‐projected model points. Additionally, an initialization technique is proposed, which locates clusters of salient features to determine the initial position and orientation of the model. Results: The proposed algorithms were evaluated based on simulations using a digital 4D CT phantom as well as experimentally acquired images of a prosthetic valve inside a chest phantom with anatomical background features. The target registration error was 0.12 ± 0.04 mm in the simulations and 0.64 ± 0.09 mm in the experimental data. Conclusions: The proposed algorithm could be used to generate 3D visualization of the prosthetic valve from two projections. In combination with soft‐tissue sensitive‐imaging techniques like transesophageal echocardiography, this technique could enable 3D image guidance during TAVR procedures.